Sex Hormones and Optic Nerve Disorders: A Review - Nuzzi, Raffaele; Scalabrin, Simona; Becco, Alice; Panzica, Giancarlo (Frontiers in Neuroscience, 2019)
Aim. This review article presents a comprehensive overview of the literature on sex hormones (estrogen, androgen, progesterone) and optic nerve disorders, with a discussion of the implications for therapy and prevention. Methods. Epidemiological, pre-clinical and clinical studies were reviewed. Results. Analysis of the biological basis for a relationship between eye diseases and sex hormones showed that some types of hormones can exert a protective effect either directly on the retina and optic nerve or indirectly by modulating ocular blood flow. For example, it seems that estrogen exposure has a protective effect against glaucoma, whereas its deficit may lead to early onset of the disease. If further studies confirm the data in the literature, estrogen therapy, because of its antioxidant action, may be effective in the treatment of Leber’s hereditary optic neuropathy, whereas, in the light of current studies, there does not seem to be an influence of estrogen on non-arteritic anterior ischemic optic neuritis (NAION). Conclusions. Although there is some evidence that in some optic nerve pathologies the sex hormones seem to play an important role there are still too few studies providing evidence for its wider use in clinical practice.